DISSIPATION AND DETERMINATION OF Spiromesifen 240SCRESIDUES IN CUCUMBER AND EFFECT OF FOOD PROCESSING ONRESIDUE - Al-Mashhadany, Wisam; Samir, Saleh; Ali, Abid Alkareem (Iraqi Journal of Science, 2024)
Laboratory and field studies were carried out at College of Agriculture-University of Baghdad and State Board for Plant Protection– Ministry ofAgriculture to study the dissipation of insecticide, [Spiromesifen] 240SC which usedto control insects on Cucumber [plastic houses] by using High Performance LiquidChromatography [HPLC] technique, besides evaluate the efficacy of sometreatments on cucumber fruits [ washing in water and soap, peeling, immersion insaline solution and pickling] to reduce the amount of insecticide residue in cucumber fruits. Results of Spiromesifen revealed that in first spray the residue inleaves was 23.65 mg/kg directly after treatment then dropped to 0.09 mg/kg after 28days. However the residue dissipated faster in second spray. In fruits, the residue infirst spray was 11.63 mg/kg directly after treatment reduced to MRL [Maximumresidue limit] in 7 days 0.19 mg/kg, however the dissipation was faster in secondspray, the residue reached MRL after 4 days 0.21 mg/kg. Regarding treatment ofwashing the fruit, Oberon residue was dissipated in first and second spray after 3days 0.21 mg/kg and 4 days 0.2 mg/kg respectively. Residue of Oberon reduced to0.04 and 0.06 mg/kg after 21 days respectively. Also, treatment of peeling, salinesolution and pickling reduced Spiromesifen residue in first spray to MRL after 2days [0.21, 0.23 and 0.22] mg/kg respectively, while in second spray, Spiromesifenreduced dropped to MRL after 2 days [0.2, 0.17 and 0.18] mg/kg respectively forprevious treatment.